Temperature-dependent conductivity of sputtered strontium stannate oxide (SSO) thin films for advanced optoelectronic applications - Abu Bakar Abd Rahman; Azza Syazwana Adzlan; Megat Muhammad Ikhsan Megat Hasnan (Faculty of Science & Natural Resources, UMS, 2024)
This study investigates the temperature-dependent electrical and optical properties of magnetron sputtered Strontium Stannate Oxide (SSO) thin films, focusing on their potential for advanced optoelectronic applications. The analysis of the current-voltage (IV) characteristics reveals a significant increase in conductivity with rising of temperature. At an applied voltage of 3.00 V to the sample device, the current rises from 2.86×10⁻⁴ A at 25°C to 8.96×10⁻⁴ A at 65°C, indicating the presence of thermally activated conduction mechanisms. The calculated activation energy is approximately 0.274 eV, which highlights the SSO thin film capability for temperature-sensitive applications, including thermal sensors and other optoelectronics devices that operate in varying thermal environments. These findings position SSO as a promising material for next-generation optoelectronic devices, offering a unique combination of performance characteristics that could drive significant advancements in the field. This study contributes to the expanding research on oxide-based transparent conductors and highlights the potential of SSO thin films in enabling future technological innovations in optoelectronics field.